Using photogrammetry to investigate coral reef erosion by clionid sea sponges - Koh, Lucas David (Nanyang Technological University, 2024)
Cliona is a genus of endolithic sponge that is steadily gaining dominance in areas such as the Caribbean Sea due to anthropogenically-caused ecosystem changes. These sponges erode and remove reef volume, reducing the carbonate budgets, structural complexity and hence ecological function of coral reefs. However, the behaviour of many Cliona species is still greatly understudied. Their erosion and lateral colonization rates have not been extensively studied in-situ, partly due to the practical difficulties in quantifying small-scale erosion over an extended time period.